A Step Forward in Identifying Socially Desirable Respondents: An Integrated Machine Learning Model Considering T-Scores, Response Time, Kinematic Indicators, and Eye Movements - Cristina Mazza; Irene Ceccato; Loreta Cannito; Merylin Monaro; Eleonora Ricci; Emanuela Bartolini; Alessandra Cardinale; Adolfo Di Crosta; Matteo Cardaioli; Pasquale La Malva; Marco Colasanti; Renata Tambelli; et al. (Human Behavior and Emerging Technologies)
Implications: Combining self-report measures with implicit data can improve SDR detection, particularly in managerial, organizational, and forensic contexts where precise assessments are crucial.